The Policy of Decentralization of Islamic Religious Education in Madrasah Tsanawiyah: A Systematic Literature Review - Annisa, Sofya Hilyatul; Madjid, Abd. (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This study discusses the problem of implementing the Decentralization of education in Indonesia, which is often hampered by the lack of attention from regional heads to education. This study aims to analyze the impact of the decentralization of education on the quality of education in Madrasah Tsanawiyah (MTs) and to understand the challenges its implementation faces. The method used was a systematic literature review, which collected data from 20 relevant articles from 2020 to 2024, taken from the Google Scholar database. The study results show that the Decentralization of education provides autonomy to local governments and schools to manage education according to local needs. However, there is still a disparity in the quality of education between regions due to differences in budget and infrastructure. The implications of this study emphasize the importance of political commitment from regional heads, capacity building of human resources, and collaboration between central and regional governments to achieve the goal of more equitable and quality education. The study also recommends stricter supervision and community participation in educational decision-making to reduce inequalities.